Cortical correlates of affective syndrome in dementia due to Alzheimer’s disease - Hayata, Thaís T.; Bergo, Felipe P. G.; Rezende, Thiago J.; Damasceno, Alfredo; Damasceno, Benito P.; Cendes, Fernando; Stella, Florindo [UNESP]; Balthazar, Marcio L. F. (Academia Brasileira de Neurologia - ABNEURO, 2015)
Neuropsychiatric symptoms in Alzheimer’s disease (AD) are prevalent, however their relationship with patterns of cortical atrophy is not fully known. Objectives To compare cortical atrophy’s patterns between AD patients and healthy controls; to verify correlations between neuropsychiatric syndromes and cortical atrophy. Method 33 AD patients were examined by Neuropsychiatric Inventory (NPI). Patients and 29 controls underwent a 3T MRI scanning. We considered four NPI syndromes: affective, apathy, hyperactivity and psychosis. Correlations between structural imaging and neuropsychiatric scores were performed by Freesurfer. Results were significant with a p-value < 0.05, corrected for multiple comparisons. Results Patients exhibited atrophy in entorhinal cortices, left inferior and middle temporal gyri, and precuneus bilaterally. There was correlation between affective syndrome and cortical thickness in right frontal structures, insula and temporal pole. Conclusion Cortical thickness measures revealed atrophy in mild AD. Depression and anxiety symptoms were associated with atrophy of right frontal, temporal and insular cortices.

Os sintomas neuropsiquiátricos na doença de Alzheimer (DA) são prevalentes, porém suas relações com padrões de atrofia cortical não são totalmente compreendidas. Objetivos Comparar padrões de atrofia cortical entre DA e controles; verificar se há correlações entre sintomas neuropsiquiátricos e atrofia cortical. Método 33 pacientes com DA foram examinados pelo Inventário Neuropsiquiátrico. Os pacientes e 29 controles foram submetidos à RNM. Consideramos quatro síndromes: afetiva, apatia, hiperatividade e psicose. Correlações entre imagens estruturais e os scores foram feitas pelo Freesurfer. Os resultados foram significantes com um valor de p < 0,05, corrigido para múltiplas comparações. Resultados Pacientes exibiram atrofia nos córtices entorrinais, giros temporal médio e inferior esquerdos, e precuneo bilateralmente. Houve correlação entre síndrome afetiva e espessura cortical em estruturais frontais direitas, ínsula e polo temporal. Conclusão Medidas de espessura cortical revelaram atrofia na DA. Sintomas de depressão e ansiedade foram associados à atrofia dos córtices frontal direito, temporal e ínsula.
Correlatos corticais da síndrome afetiva na demência da doença de Alzheimer
Keywords: Depression; Anxiety; MRI; Neurodegenerative disease; Neuropsychiatry; Depressão; Ansiedade; RNM; Doença neurodegenerativa; Neuropsiquiatria